In the Shower Actually: Using Podcasts to Support Communicative Competence in Upper Secondary School English - Daði Þór Pálsson 1993- (2021)
Existing research has shown that Icelandic students tend to be more competent in terms of receptive skills than productive skills in English, and that students often overestimate their English language abilities. Prior research has also shown that Icelandic upper secondary schools may not be providing students with adequate opportunities to practice their oral production skills. A design-based research (DBR) project focusing on the potential of using student-created podcasts to support communicative competence for students in upper secondary English in Iceland was conducted in response to these issues. Teaching materials for supporting oral production and communicative competence were developed and tested in an upper secondary English course, and the utility of this educational intervention was evaluated. The intervention involved both a teacher-created and student-created podcasts, and this thesis highlights some of the main pedagogical theories and strategies used to design the intervention. Results on teacher opinions of the intervention were gathered through semi-structured interviews and results on student opinions and satisfaction were gathered through a survey. Results were positive in both instances, with teacher and students reporting high satisfaction and a number of perceived benefits regarding the use of podcasts in the language learning process. Additionally, all the necessary materials and information for other upper secondary English teachers to use the teaching materials in their own classrooms are provided in the Appendix.